Television-Based Teaching in the Pacific Area in Northern Samar :Inputs for Sustainable Integration - Mendez, Krisa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the implementation of Television-Based Teaching (TBT) in selected public elementary schools in the Pacific towns of Northern Samar and generated strategic inputs for its sustainable integration. Anchored on Mayer’s Cognitive Theory of Multimedia Learning, Bandura’s Social Cognitive Theory, Stufflebeam’s CIPP Evaluation Model, Rogers’ Diffusion of Innovations Theory, Sweller’s Cognitive Load Theory, Media Richness Theory, and the Quality Teaching Model, the study employed a descriptive-evaluative research design guided by the Input-Process-Output framework. Data were collected through a researcher-made questionnaire administered to public elementary school teachers directly involved in TBT implementation. Proportional sampling was used to obtain respondents from selected schools in Laoang, Palapag, Mapanas, Gamay, and Lapinig, and the data were analyzed using weighted mean and descriptive statistical techniques. Findings revealed that schools generally possessed functional television hardware, satisfactory broadcast signal strength, and adequate power supply to support TBT. Teachers demonstrated satisfactory to high levels of pedagogical competence in curricular contextualization, technology-enhanced classroom management, and instructional facilitation. Synchronization between televised lessons and classroom instruction was generally effective, contributing to learner engagement and instructional continuity. However, implementation remained affected by unstable signal reception, power interruptions, limited technical support, transportation difficulties, insufficient maintenance resources, lack of standardized troubleshooting procedures, and heavy ICT coordinator workloads. The study concluded that TBT remains a viable and effective instructional approach for geographically isolated schools but requires stronger instructional, technical, and administrative support systems to ensure long-term sustainability. Recommended interventions include infrastructure enhancement, localized instructional materials, preventive maintenance programs, technical support mechanisms, dedicated funding, and continuous monitoring and evaluation. The study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting equitable access to learning opportunities in geographically isolated communities and SDG 10: Reduced Inequalities by addressing educational disparities associated with geographic and infrastructural limitations. Its sustainability impact lies in strengthening institutional capacity, instructional continuity, and long-term educational resilience in resource-constrained schools.
Keywords: Broadcast Signal Strength; Curricular Contextualization; Instructional Facilitation; Pedagogical Competence; Sustainable Integration; Television-Based Teaching; Technology-Enhanced Classroom Management